Comparação entre metodologias para avaliar a idade à primeira concepção em éguas puro-sangue inglês - Mota, M. D. S. [UNESP]; Taveira, R. [UNESP]; Oliveira, H. [UNESP] (SciELO Espana/Repisalud, 2011)
In Brazil, due to the breeding season for Thoroughbred, the reproductive data are normally truncate, since the breeders try to get animals that were born at the beginning of the breeding season in order to take their competitive advantages (more developed, mature and trained animals) compared to animals born later in the same breeding season. To analyze these data suitable methods should be used. Then, this paper aims to compare three methodologies: the method of maximum restricted likelihood, using MTDFREML, bayesian analysis without censured data by software MTGSAM and bayesian analysis with censured data by software LMCD, to evaluate age at first conception in thoroughbred mares, in order to verify its impact on the choice of stallions during selection. The database contained 3509 records for age at first conception (months) for thoroughbred mares. The heritability estimates were 0.23, 0.30 and 0.0926 (log scale), for MTDF, MTGSAM and LMCD, respectively. Considering all animals in the pedigree (6713), ranking correlations varied from 0.91 to 0.99. When only stallions were considered (656), those varied from 0.48 to 0.99 (considering different percentages of selected males) between evalua-tion methods. The highest changes in the general classification were observed when LMCD was compared to the other two methods. As the linear censured model is the most suitable for trait analysis with censured data, it was observed that censure information would lead to the choice of different animals during the selection process, when compared to the two other methodologies.
Comparison among methodologies for evaluation of age at first conception in thoroughbred mares
Keywords: Censured data; Equine; Reproduction; Animalia; Equidae